Spinal Motocross Injuries in the United Kingdom. Issue 1 (9th January 2018) - Singh, Rohit; Bhalla, Amit; Ockendon, Matthew; Hay, Stuart
Background: Motocross is a form of motorcycle racing held on established off-road circuits and has been a recreational and competitive sport across the world for >100 years. In the United Kingdom alone, motocross has grown into a phenomenally ambitious and popular franchise. There are >200 motocross clubs across the country, permitting >900 events annually. Purpose: To assess the current trend of spine-related motocross injuries over the past 5 years. Study Design: Descriptive epidemiology study. Methods: Data were prospectively collected over 5 years (August 2010–August 2015) at our regional trauma and spine unit, regardless of whether the rider was performing the sport competitively or recreationally. Results: During the study period, spine-related injuries were identified for 174 patients (age range, 6-75 years) who were directly referred to our department following recreational or competitive motocross, with most injuries being sustained within the early spring and summer months, representing the start of the motocross season. A significant number of injuries were in males (n = 203, 94%), with the majority of injuries occurring within the 21- to 30-year-old age group. A total of 116 (54%) injuries required operative treatment. The most common spinal injury was thoracolumbar burst fracture (n = 95), followed by chance fractures (n = 26). Conclusion: This data series emphasizes the prevalence and devastation of motocross-related spinal injuries in the United Kingdom and may serve in administering sanctions and guidelines to governing bodies of motocross. The spinal injuries that occur during motocross have significant capital connotations for regional spinal centers. The recent surge in motocross popularity is correlated with the number of injuries, which have increased over the past 5 years by almost 500%.